1999
DOI: 10.1119/1.19144
|View full text |Cite
|
Sign up to set email alerts
|

Student understanding of light as an electromagnetic wave: Relating the formalism to physical phenomena

Abstract: During an investigation of student understanding of physical optics, we found that some serious difficulties that students have with this topic may be due, at least in part, to a lack of understanding of the nature of light as an electromagnetic wave. We therefore decided to look carefully at how students interpret the diagrammatic and mathematical formalism commonly used to represent a plane EM wave. The results of this research have guided the development and modification of tutorials that address some of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 14 publications
4
52
0
2
Order By: Relevance
“…Hake found that students in the latter courses averaged gains that were twice as large as those in the traditional classes (Hake, 1998(Hake, , 2002. Results consistent with these have since been obtained by numerous other physics research groups (Ambrose et al, 1999;Redish, 2003;Heron et al, 2003;Loverude et al, 2003). Interactive engagement of students in their own learning measurably enhanced the conceptual development and problem-solving abilities of the learners.…”
Section: Classroom Studiessupporting
confidence: 70%
“…Hake found that students in the latter courses averaged gains that were twice as large as those in the traditional classes (Hake, 1998(Hake, , 2002. Results consistent with these have since been obtained by numerous other physics research groups (Ambrose et al, 1999;Redish, 2003;Heron et al, 2003;Loverude et al, 2003). Interactive engagement of students in their own learning measurably enhanced the conceptual development and problem-solving abilities of the learners.…”
Section: Classroom Studiessupporting
confidence: 70%
“…This theoretical article is about the teaching and learning challenges that arise from students experiencing this partiality of representations, where important physics aspects are not initially discernible. These issues are educationally important because what creates a powerful communicative system for physics at the same time manifests in the difficulties students experience in terms of becoming "fluent" [2] (p. 28) in the disciplinary-specific representations [2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Theoretical details from the literature, together with the concept of disciplinary affordance [11,12], are used to underpin a case that physics representations need to be "unpacked" for students.…”
Section: Introductionmentioning
confidence: 99%
“…1(b)] has likely contributed to the formation of certain misconceptions, such as the belief that the fields only exist in the regions formed by the field vectors and the sine curve [ Fig. 1(b)] [6][7][8]. It is also well known that introductory physics students often have great difficulty correctly interpreting the canonical velocity vs time and acceleration vs time diagram [9].…”
Section: Introductionmentioning
confidence: 99%